Italian Mafia-style organizations and the firearms trafficking. Reflections on some judicial experiences (Rivista di Studi e Ricerche sulla criminalità organizzata, 2018)
This article deals with the role of the Italian Mafia Organizations in illicit firearms trafficking. The author offers an overview of several criminal investigations, especially involving ’ndrangheta and camorra affiliates, in illicit firearms trafficking. This study contends that there is no a hegemonic Italian Mafia Group governing illicit firearms trafficking, and that this criminal activity (which in most cases does not represent, per se, the main goal of the Organization) constitutes a very powerful instrument to strengthen operational capacities of Mafia Organizations to commit other crimes, such as illicit drugs trafficking.Keywords: Illicit firearms trafficking, criminal investigations, mafia-type organizations, illegal routes, Balkans